Perennial ryegrass and novel festulolium forage grasses in the tropical highlands of Central Kenya: Preliminary assessment - Mwendia, Solomon W.; Maass, Brigitte L.; Njenga, David; Notenbaert, An Maria Omer (International Center for Tropical Agriculture, 2019)
Two perennial ryegrass (Lolium perenne) varieties and 5 festulolium hybrids (L. perenne × Festuca spp.) were evaluated on-farm for their performance over one growing season on clay loam soils at Ol-joro-Orok in the central highlands of Kenya at about 2,600‒2,800 masl. Seed was sown in May 2015 and fertilizer (90 kg N + 90 kg P/ha) was applied at planting. The study continued for 8 months with harvests after 113, 99 and 32 days (3 growth cycles). Growth attributes assessed included dry matter yield (DMY) and plant height, while forage nutritive value was measured in terms of crude protein (CP), acid detergent fiber (ADF) and neutral detergent fiber (NDF) concentrations. At the end of the first growth cycle, 61 local dairy farmers rated the grasses on criteria they nominated as being important, including DMY, growth rate, height, frost tolerance, disease tolerance and leafiness. Total herbage yields for the whole study period (8 months) ranged from 14.6 to 18.0 t DM/ha for perennial ryegrass and 14.3 to 20.9 t DM/ha for festulolium with very poor growth in the third growth cycle. All perennial ryegrass and festulolium lines contained similar (P>0.05) concentrations of CP (163–190 g/kg DM), ADF (264–281 g/kg DM) and NDF (448–493 g/kg DM). For perennial ryegrass, farmers gave a minimum weighted score of 6.7 and for festulolium, 7.9. Based on herbage production, forage nutritive value and farmers’ assessments, we conclude that all perennial ryegrass and festulolium lines tested have the potential to contribute to improving the forage resource base in this and other similar areas, especially for farmers whose land sizes allow grazing instead of stall-based feeding only. Further studies with N applications after each harvest would determine whether yields can be maintained at high levels for longer than in this study, while grazing and feeding studies would determine how well the pastures support weight gains and milk yields. Studies over a number of years are needed to assess how persistent these varieties/hybrids are in this and other environments.